Studio Perancangan Arsitektur Kota: Kampung Wisata Hijau Organik Cilegong, Desa Mekarwangi - Muhammar Khamdevi; Danang Harito Wibowo (Universitas Serang Raya, 2018)
The formal housing expansion by private property developers in Tangerang District has the potential to generate